Synergistic removal of emerging contaminants using bacterial augmented floating treatment bed system (FTBs) of Typha latifolia and Canna indica for rejuvenation of polluted river water - Patel, Vandan; Sharma, Shruti; Desai, Chirayu; Kikani, Bhavtosh; Madamwar, Datta (Frontiers in Microbiology, 2025)
IntroductionFloating Treatment Bed systems (FTBs) provide an effective approach to remove pollutants from the rivers. These systems consist of aquatic plants anchored on mats, which support the growth of microbial communities. Such a synergy between plants and microbes in FTBs plays a pivotal role to improve efficacy of river restoration strategies.MethodologyThe effectiveness of the FTBs was evaluated for the rejuvenation of polluted water from the Mini River in Gujarat, India. These systems consisted of wetland plants, either Typha latifolia or Canna indica, which were augmented with the bacterial consortium VP3. Furthermore, the 16S rRNA gene amplicon sequencing approach identified the dominant bacterial communities and relative microbial community shifts within the FTBs. The presence of emerging contaminants, antimicrobial resistance genes, and pathogenic bacterial species in the untreated river water was evaluated, along with their reduction following treatment through FTBs. This analysis yielded important insights into the microbial dynamics governing the reduction of these contaminants.Results and discussionThe bacterial augmented FTBs consisting wet plants achieved reduction of 57%, 70%, 74%, and 80% in biochemical oxygen demand (BOD), chemical oxygen demand (COD), total phosphate, and sulfate, respectively. Moreover, the 16S rRNA gene amplicon sequencing identified Proteobacteria as the dominant phylum, with Pseudomonas species and Hydrogenophaga species being the most abundant genera in FTBs containing T. latifolia and C. indica, respectively. The functional gene prediction indicated presence of various xenobiotic degrading genes too. Non-targeted LC-HRMS analysis of treated water demonstrated complete elimination of antibiotic derivatives and dye intermediates, along with the partial removal of pharmaceutical and personal care products (PPCPs) and chemical intermediates. Additionally, the abundance of probable pathogenic bacteria and dominant antibiotic resistance genes was significantly reduced upon treatment. The phytotoxicity analysis of the treated water supported the outcomes. The studies on removal of emerging contaminants in the polluted river ecosystem has been relatively less explored, highlighting novelty and future possible applications of the plant-microbial augmented FTBs in rejuvenation of polluted rivers.